COMPARISON OF SOME PHYSICAL, SKILL AND FUNCTIONAL ABILITIES OF FUTSAL AND OPEN FOOTBALL PLAYERS - Kareem Naeemah Rahan (Proximus Journal Publishing, 2024)
The importance of the research was evident in the study of some of the physical abilities and functional skills of the two teams of the Al-Manara University for Medical Sciences are (halls and open) to show the differences between them in the variables and what is the differentiation between the halls and open and from here the importance of the research to clarify the differences in order to correct the training process and choose exercises and training method to suit them to improve and develop the performance of the players and their abilities and physical, skill and functional capabilities. In regards to the issue of research, it aims to provide solutions for workers in the training field and players by identifying their weaknesses and strengths. This will enable them to address these weaknesses, continue their training, and understand the differences between futsal players and open field players. Additionally, the research highlights the lack of achievements in Iraqi university championships. The research attempted to discern the disparities in physical capacities, fundamental skills, and functional assessments between players of the halls and open. The researcher employed a descriptive strategy inside the survey method to address the research problem. The researcher determined that futsal players exhibit greater strength in their individual legs and explosive power compared to open players. However, open players demonstrate superiority over futsal players in functional indicators such as resting heart rate and breathing rate per minute
Keywords: Comparison; Physical Skill; Functional Abilities